Estudio de prescripción-indicación de fentanilo en la unidad de cuidados intensivos - Hospital de Alta Complejidad Virgen de la Puerta, 2016 - Solano Palacios, Jorge Luis (2018)
In the present work, the characteristics of the fentanyl prescriptions used in the most frequent indications made in the Intensive Care Unit of the High Complexity Virgen de la Puerta Hospital during 2016 were determined. We analyzed 150 prescription prescriptions of fentanyl from the total number of properly issued prescriptions and reviewed the clinical histories of the patients as well as the ICD- 10 of each diagnosis, giving the following results: the most frequent indications with fentanyl prescription were acute respiratory failure (J960) and non-specific respiratory failure (J969), represented by 36.6% and 17.5% respectively, of the total special recipes issued. It was also determined that the prescription of fentanyl was higher in adults in the range of 61 to 80 years, represented by 41.3%, and prescriptions made to male patients with 63.3% and female with 36.7%. And finally, the therapeutic indications, route of administration, dose and duration of treatment were determined, being sedation / analgesia with 50%, the one with the highest prescription of fentanyl, being administered mostly via IV in Bolus: 0.001 to 0.002 mg / kg with an average treatment duration of 7 days. From the results found, it is concluded that the most frequent indication with prescription of fentanyl is acute respiratory failure and it occurs mostly in males around 61-80 years, with sedation / analgesia being the therapeutic indication of greater use via IV with an average treatment duration of 7 days